Occurrence of different persistent organic pollutants in Atlantic cod (Gadus morhua L.) in Icelandic waters - Vordís Baldursdóttir (2011)
Persistent organic pollutants (POPs) can have various harmful effects on the health of living organisms. They can be carcinogenic, affect the hormonal balance, the nervous system and the reproductive system. POPs have very long half lives in the environment and in living organisms, they are very lipophilic and accumulate in the food chain. Therefore, it is necessary to monitor these substances in nature. The main objective of this project was to analyse the levels of some POPs in the Icelandic cod (Gadus morhua) and evaluate the effect that different factors such as; sex, age, sexual maturation, location of catch, season, have on these levels. In addition, to assess whether the analytical method that has been developed in our laboratory gives comparable results to other researchers. Eleven POPs were analysed in the muscles from 64 individual cods and 38 livers from these same individuals. The amount of POPs detected in the cod was far below the previously set maximum levels in food Iceland. The levels observed in the liver were about 300 times higher than in the muscle, reason for this is that these substances are lipophilic and the muscle contains very little fat. The analytical method was found to be comparable to methods used by other researchers, and appears to be adequate for the same substances in chicken. There is a need for further studies regarding the amount of POPs in other marine species as well as other organisms that feed on fish based products such as fish meal and are used for human consumption. Keywords: POPs, PCBs, pesticides, Atlantic cod (Gadus morhua), traceability, PSE (pressurised solvent extraction) Rannsóknir hafa sýnt að þrávirk lífræn efni geta haft margvísleg skaðleg áhrif á heilsu lífvera. Þau geta m.a. verið krabbameinsvaldandi, haft áhrif á hormónabúskap, taugakerfi og æxlunarfæri. Þrávirk lífræn efni brotna hægt niður í umhverfinu og í lífverum, þau eru afar fituleysin og magnast að styrk upp fæðukeðjuna og því er nauðsynlegt að fylgjast vel með efnunum í náttúrunni. Helsta ...